Not only history : proceedings of the Conference in Honor of Mario Liverani held in Sapienza-Università di Roma, Dipartimento di scienze dell'Antichità, 20-21 April 2009 - Bartoloni, Gilda; Biga, Maria Giovanna; Bramanti, Armando; Liverani, Mario (Eisenbrauns, 2016)
In 2009, Mario Liverani celebrated his 70th birthday and retired from teaching at Sapienza-Università di Roma, although his book Antico Oriente: Storia, società, economia remains in wide use and is still foundational for anyone studying the ancient Near East. The Dipartimento di Scienze Storiche, Archeologiche e Antropologiche dell'Antichità, where Mario Liverani was a leading specialist since the department's inception, celebrated Liverani's milestone birthday and retirement with a conference held in his honor, and this book publishes the papers that were read at the conference on April 20-21.